2010
DOI: 10.3354/meps08441
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical environmental conditions on the patch dynamics of Dictyota pulchella and Lobophora variegata on Caribbean coral reefs

Abstract: Trends in the percentage cover of macroalgae are generally used as an important indicator of the health of coral reefs. While considerable data exist on patterns of macroalgal cover, the underlying patch dynamics of macroalgae are poorly understood. It is important to appreciate the dynamical processes of algae because they determine the frequency and duration of competitive interaction with other taxa, such as corals, and thereby contribute to our understanding of competitive interactions. We used transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 54 publications
1
41
0
Order By: Relevance
“…Macroalgal communities on coral reefs can show noticeable temporal changes in species composition and abundance, associated with abiotic (e.g., temperature, light) and biotic factors (Tsai et al, 2005; Renken et al, 2010; Page-Albins et al, 2012). Some common species in the Caribbean such as Dictyota spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macroalgal communities on coral reefs can show noticeable temporal changes in species composition and abundance, associated with abiotic (e.g., temperature, light) and biotic factors (Tsai et al, 2005; Renken et al, 2010; Page-Albins et al, 2012). Some common species in the Caribbean such as Dictyota spp.…”
Section: Discussionmentioning
confidence: 99%
“…and Halimeda spp. increase in abundance during summer, often covering over 50% of the benthos, while others (e.g., turf-forming species) are more abundant during cooler periods of the year (Lirman & Biber, 2000; Renken et al, 2010; Ferrari et al, 2012). In our study, we found an increase in overall abundance of macroalgal recruits towards spring with distinct species flourishing within treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature and wave energy, for example, are some of the variables that can be measured through satellites and heavily influence pattern and process in marine systems. These factors not only determine the global distribution of reefs [282], but the distribution of reef habitats e.g., [154], reef biodiversity e.g., [42], reef processes e.g., [283], and the impact of disturbance and the recovery of reef ecosystems e.g., [209].…”
Section: Mapping Environmentsmentioning
confidence: 99%
“…In temperate rocky shore ecosystems, wave exposure drives photosynthesis in intertidal macroalgae (e.g., Hepburn et al 2007), influences macroalgal morphology (e.g., Wernberg and Thomsen 2005), and ultimately regulates trophic structure and ecological dominance among rocky intertidal algal communities (e.g., Dayton 1975;Mcquaid and Branch 1985). In tropical coral ecosystems, productivity is generally higher on windward than leeward reefs (Marsh 1970), enhancing coral growth rates (Barnes 1983), and influencing macroalgal patch dynamics (Renken et al 2010). Despite such strong ecological regulation, surprisingly, little is known about the influence of wave exposure on the shortterm dynamics of macroalgal phase shifts following disturbance.…”
Section: Communicated By Biology Editor Dr Mark Vermeijmentioning
confidence: 98%